Pengembangan Media Pembelajaran Animasi Videoscribe Pada Mata Pelajaran Geografi Materi Pengelolaan Sumber Daya Alam Indonesia - Rahim, Dicky A.; Eraku, Sunarty S.; Mohamad, Nurdin (Geosfera: Jurnal Penelitian Geografi, 2022)
This research is a research that aims to develop an animated learning media Videoscribe on Natural Resources Management material. Videoscribe is one of the most effective tools to use to make complex concepts more interesting and fun. The research method is the ADDIE method. The ADDIE model is a learning design/model that can facilitate students in developing the scientific process, is flexible. The location of the research is carried out at SMA Negeri 1biluhu. Data collection methods are observation, interviews, questionnaires, documentation. This study uses two types of data, namely quantitative data and qualitative data. This learning media was tested on a limited basis to the number of students 26 students from a total of 63 students in SMA Class XI Social Sciences using a questionnaire. The data collected is in the form of research results regarding the quality of learning media as well as suggestions for product revision. The validation results from material experts show that the media validation value given by validator 1 or material / content expert with a very valid category is 92%, validator II or product design expert provides a valid assessment of 79% while validator III or subject matter expert in this case is a teacher of geography lessons to give an assessment with a very valid category that is equal to 100%. The average student response to learning media is 87%..This research is a research that aims to develop an animated learning media Videoscribe on Natural Resources Management material. Videoscribe is one of the most effective tools to use to make complex concepts more interesting and fun. The research method is the ADDIE method. The ADDIE model is a learning design/model that can facilitate students in developing the scientific process, is flexible. The location of the research is carried out at SMA Negeri 1biluhu. Data collection methods are observation, interviews, questionnaires, documentation. This study uses two types of data, namely quantitative data and qualitative data. This learning media was tested on a limited basis to the number of students 26 students from a total of 63 students in SMA Class XI Social Sciences using a questionnaire. The data collected is in the form of research results regarding the quality of learning media as well as suggestions for product revision. The validation results from material experts show that the media validation value given by validator 1 or material / content expert with a very valid category is 92%, validator II or product design expert provides a valid assessment of 79% while validator III or subject matter expert in this case is a teacher of geography lessons to give an assessment with a very valid category that is equal to 100%. The average student response to learning media is 87%..